2011
DOI: 10.1590/s1982-45132011000300005
|View full text |Cite
|
Sign up to set email alerts
|

Estimativa da perda de solo por erosão hídrica na bacia hidrográfica do rio Jauru/MT

Abstract: A crescente ocupação do sudoeste de Mato Grosso tem provocado o desmatamento de grande parte da vegetação natural para a exploração agropecuária, sem o adequado uso e manejo do solo, originando áreas de alta fragilidade ambiental e suscetibilidade à erosão hídrica. Para estimar a perda de solo na Bacia Hidrográfica do rio Jauru foi utilizada da Equação Universal de Perdas de Solo operacionalizada por meio de Geotecnologias. No período de 1994 a 2003, a perda média de solo foi de 3,26 t ha-1 ano-1, corresponden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
11

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 1 publication
0
5
0
11
Order By: Relevance
“…, studying Neosols in the municipality of São Vicente, Rio Grande do Norte State, observed that the clay content increased in subsurface and that this increase is probably due to the smaller size of the surface clay particles, which are easily transported by water and deposited in lower landscape locations. Neves et al (2011), conducting research on soil erosion losses in the Jaruru river basin in the State of Mato Grosso, observed that the Quartzarenic Neosols present a high risk of soil loss, which is due to slope and ramp length, accelerating the erosive process and, consequently, the soil degradation. Note.…”
Section: Resultsmentioning
confidence: 99%
“…, studying Neosols in the municipality of São Vicente, Rio Grande do Norte State, observed that the clay content increased in subsurface and that this increase is probably due to the smaller size of the surface clay particles, which are easily transported by water and deposited in lower landscape locations. Neves et al (2011), conducting research on soil erosion losses in the Jaruru river basin in the State of Mato Grosso, observed that the Quartzarenic Neosols present a high risk of soil loss, which is due to slope and ramp length, accelerating the erosive process and, consequently, the soil degradation. Note.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, these events represent almost the entire erosion of the areas. Neves et al (2011) evaluated watersheds in southwestern Mato Grosso State and found 78% of soil losses in pasture areas over a Red Argisol. Almeida et al (2012) evaluated soil loss in the Brazilian semiarid region and found reduction of 68% in runoff after ten years of fallow, compared to a degraded area.…”
Section: Wp -Water Precipitation; Ep -Effective Precipitationmentioning
confidence: 99%
“…Water erosion is the result of the interaction of precipitations, soil, topography, soil coverage and conservation practices (WISCHMEIER; SMITH, 1978), and is an emerging subject among researchers, since it interferes directly on agricultural productivity and causes economic and environmental damages (KANG et al, 2001;LOBATO et al, 2009;NEVES et al, 2011;TELLES et al, 2011). The quantification of water erosion and information on the physical processes related to it is crucial for develop means to maximize the use of the water resources available and avoid the negative effects of soil erosion (SILVA et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…This estimates the average soil loss for long periods of time caused by laminar water erosion and is a practical model because it uses parameters that are easy to obtain. This indirect model is the most currently employed in this context, and it is observed in various scientific research studies such as CORREA et al (2007), AVANZI et al (2008), SILVA et al (2010), NEVES et al (2011), ZHANG et al (2011) and MENESES (2014.…”
Section: Introductionmentioning
confidence: 99%